(untitled) (Research, Society and Development, 2020)
We aimed investigate the effects of 45 min of ischemia followed by 72 h of intestinal reperfusion (IR) in the ileum, liver, lungs, and kidneys in Wistar rats and the responses of these organs to curcumin treatment. Ischemia was induced by occluding the superior mesenteric artery. Rats were treated orally with 40 mg/kg curcumin. We analyzed oxidative stress and inflammation in the ileum, liver, lungs, and kidneys. Intestinal IR led to a reduction of reduced glutathione levels in the intestine, lungs, and kidneys and increased lipid hydroperoxide levels in all organs. An increase in the enzymatic activity of catalase was observed in all organs, and an increase in superoxide dismutase activity was observed in the ileum and lungs. Glutathione s-transferase levels increased only in the kidneys. Myeloperoxidase increased in all four organs, and n-acetyl-glycosaminidase increased only in the ileum and lungs. Curcumin prevented all of the changes in the ileum and liver. In the lungs, curcumin had no effect on n-acetyl-glycosaminidase. Curcumin did not prevent the changes in reduced glutathione, lipid hydroperoxides, or myeloperoxidase in the kidneys. Intestinal IR caused oxidative stress and inflammation in the ileum, lungs, and kidneys and to a lesser degree in the liver. Because of its systemic distribution, curcumin prevented changes mainly in the ileum, lungs, and liver and to a lesser degree in the kidneys.